Influence of Coarse Aggregate Concentration on the Frost Resistance of Non-Air-Entrained Concrete - Jiwei Cai; Donghui Wang; Gelong Xu; Qing Tian; Shaokun Guo (Journal of Engineering)
Aggregate-interlocking concrete is a kind of low-carbon and high-performance concrete, while the aggregate-interlocking concrete prepared by the distributing-filling coarse aggregate (DFCA) process worsens frost resistance than ordinary concrete. In order to better apply the aggregate-interlocking concrete, it is necessary to figure out the relationship between the frost resistance and the coarse aggregate concentration. In the study, three series of concretes, C30, C40, and C50, are designed, and the charge passed, scaling mass, water uptake, and penetration depth of NaCl solution are tested as indicators to account for the relationship between frost resistance and coarse aggregate concentration. The results indicate that aggregate still has a strong restraint effect on the permeability of concrete after freezing-thawing cycling, but compared to the unfrozen concrete, the charge passed of the concrete with higher aggregate concentration tends to increase more intensively. The scaling happens at both bulk mortar and interfaces between aggregate and mortar. The increase in aggregate concentration could restrain the scaling of mortar, but excessive aggregate concentration results in a significant increase in scaling mass. The concrete with higher coarse aggregate concentration could absorb more water during the freezing-thawing cycling, and the penetration depth of NaCl solution also increases with the increase of coarse aggregate concentration. The results reveal that the increase in aggregate concentration degrades the frost resistance of concrete, and the DFCA process could be applied in high-strength concrete to mitigate the negative effect of coarse aggregate on the frost resistance of concrete.